Formulation development and analytical evaluation of α-CGRP 8-37 for a potential subcutaneous psoriasis therapy - Magnason,Máni Þór (2026)
α-CGRP 8-37 is a peptide fragment of calcitonin gene-related peptide and is commonly used as a CGRP antagonist in pharmacological research. CGRP signaling has been discussed in relation to neuroimmune mechanisms in psoriasis, but a practical development of α-CGRP 8-37 requires analytical methods and formulation strategies that can handle peptide instability, adsorption, and matrix effects. The aim of this thesis was to develop and evaluate analytical and formulation approaches for α-CGRP 8-37, with emphasis on subcutaneous formulation relevance and pilot blood-matrix method development. An HPLC method with UV detection at 214 nm was used for formulation and stability samples. LC-MS was used for pilot blood-matrix experiments. Formulation studies evaluated α-CGRP 8-37 in aqueous and excipient-containing vehicles at different peptide concentrations during room-temperature storage. An adsorption experiment compared apparent peptide recovery in BSA-coated and non-coated vials. Blood-matrix experiments tested dilution and protein-removal ap-proaches, including direct dilution into aqueous formic acid, inhibitor-containing formic acid, and organic solvent, with and without SPE cleanup. The formulation data showed concentration-dependent differences in apparent stability. At day 41, 10 and 20 mg/mL samples retained mean signals of 55.0% and 58.2% across tested condi-tions, while 2 mg/mL samples retained a mean signal of 15.3%, with several conditions becom-ing undetectable. BSA-coated vials increased apparent recovery in several low-concentration samples, supporting adsorption as a likely contributor to peptide loss. In the first whole-blood LC-MS pilot, CGRP and CGRP 8-37 signals for 30 second old samples were approximately 19.1% and 24.5% of blank-spiked controls, and signals decreased by 84.6% and 79.5%, respec-tively, from 30 seconds to 10 min. In the SPE-based experiment, enzyme inhibitor containing unspiked samples gave a high CGRP 8-37 signal while CGRP remained low. Likely indicating that sample preparation chemistry strongly affected the measured peptide signal. The HPLC method was suitable for formulation screening, while the current blood-matrix LC-MS workflow was not ready for quantitative volunteer or patient analysis. The blood results should be interpreted as method development findings rather than biological concentration data. Future work should prioritize internal standards, controlled quenching immediately after blood draw, recovery studies, matrix-factor assessment, pH and osmolality testing, and longer formu-lation stability studies.
Keywords: psoriasis; formulation; peptide; analytical methods; stability; pharmaceutical formulation